Pseuduvarines A And B,two New Cytotoxic Dioxoaporphine Alkaloids From Pseuduvaria Rugosa - Hairin Taha; A Hamid A Hadi; Noraziah Nordin; Ibrahim A Najmuldeen; Khalit Mohamad; Osamu Shirota; Alfarius E Nugroho; Wong Chin Piow; Toshio Kaneda; Hiroshi Morita (Pharmaceutical Society of Japan, 2024)
Volume 59 Issue 7